Consistency of supervisor and peer ratings of assessment interviews conducted by psychology trainees. Issue 5 (19th October 2016) - Gonsalvez, Craig J.; Deane, Frank P.; Caputi, Peter
ABSTRACT: Observation of counsellor skills through a one-way mirror, video or audio recording followed by supervisors and peers feedback is common in counsellor training. The nature and extent of agreement between supervisor–peer dyads are unclear. Using a standard scale, supervisors and peers rated 32 interviews by psychology trainees observed through a one-way mirror. Results indicated that peers and supervisors used similar dimensions to cluster the various competencies. Peers rated counsellor performance more positively for general counselling skills, but not for specialised techniques. Analyses revealed good supervisor–peer agreement for some items and poor agreement on others, with some differences being unacceptably large. The study has important implications for how feedback involving supervisors and peers might be managed and for peer supervision models.